Process safety management for storage facilities. (U.S. Department of Labor, Occupational Safety and Health Administration, 2017)
OSHA 3909-03 2017 Process Safety Management for Storage Facilities Occupational Safety and Health Act of 1970, To assure safe and healthful working conditions for working men and women; by authorizing enforcement of the standards developed under the Act; by assisting and encouraging the States in their efforts to assure safe and healthful working conditions; by providing for research, information, education, and training in the field of occupational safety and health. This guidance document is not a standard or regulation, and it creates no new legal obligations. It contains recommendations as well as descriptions of mandatory safety and health standards. The recommendations are advisory in nature, informational in content, and are intended to assist employers in providing a safe and healthful workplace. The Occupational Safety and Health Act requires employers to comply with safety and health standards and regulations promulgated by OSHA or by a state with an OSHA approved state plan.
"OSHA 3909-03 2017"
Keywords: Storage facilities -- United States -- Safety measures.; elektronické knihy; electronic books